Sunday
March 26, 2017

Post a New Question

Posted by on .

Solve by using elimination:

7x - 2y =3
2x +y = 4

?????????????????

  • MATH - ,

    (1) 7x - 2y =3
    (2) 2x + y = 4

    look to see which variable is easier to get rid of. since the first equation has -2y, multiple the 2nd equation by 2, so that you get 2y. -2y + 2y = 0, so you will have eliminated the y variable

    Multiple (2) by 2
    2 (2x + y = 4) = 4x + 2y = 8

    Add the two equations together
    7x - 2y = 3
    4x + 2y = 8
    11x + 0 = 11
    11x = 11
    x = 1

    Substitute x = 1 in either equation (1) or (2) to find y.

    7x - 2y = 3
    7(1) - 2y = 3
    7 - 2y = 3
    2y = 4
    y = 2

    To check
    substitute x = 1, y = 2
    in the other equation (1)
    2x + y = 4
    2(1) + 2 = 4
    2 + 2 = 4
    4 = 4
    so it's correct

  • MATH - ,

    Thanks a lot:D

  • MATH - ,

    you're welcome

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question